Applied Hugging Face. (Pragmatic AI Solutions, 2022)
Applied Hugging Face Learn to use Hugging Face to solve real-world problems 1.0 Introduction to Applied Hugging Face Course 1.1 Introduction to Hugging Face Hub: models, datasets, spaces and access tokens 1.2 Using GPU enabled Codespaces 1.3 Using Hugging Face CLI 1.4 Working with Datasets 1.5 Working with Models 2.0 Introduction to Transformers and Fine-tuning vs Supervized Learning (Transfer Learning) 2.1 Using Hugging Face with GitHub GPU-enabled Codespaces for Fine-tuning 3.0 Introduction to Hugging Face Spaces 3.1 Using Hugging Face Spaces 3.2 Deploying Hugging Face Spaces applications with GitHub Actions Topics Covered Include: Hugging Face Hugging Face Models Hugging Face Transformers Hugging Face Spaces Hugging Face Datasets GPU-enabled GitHub Codespaces OpenAI Whisper Hugging Face Tutorial Additional Popular Resources Pytest Master Class AWS Solutions Architect Professional Course Github Actions and GitOps in One Hour Video Course Jenkins CI/CD and Github in One Hour Video Course AWS Certified Cloud Practitioner Video Course Advanced Testing with Pytest Video Course AWS Solutions Architect Certification In ONE HOUR Python for DevOps Master Class 2022: CI/CD, Github Actions, Containers, and Microservices MLOPs Foundations: Chapter 2 Walkthrough of Practical MLOps Learn Docker containers in One Hour Video Course Introduction to MLOps Walkthrough AZ-900 (Azure Fundamentals) Quick reference guide 52 Weeks of AWS Episode 8: Infrastructure as Code with CDK and AWS Lambda Learn GCP Cloud Functions in One Hour Video Course Python Devops in TWO HOURS! MLOps Platforms From Zero: DatMLOps Platforms From Zero: Databricks, MLFlow/MLRun/SKLearn AWS Machine Learning Certification In ONE HOUR Fast, documented Machine Learning APIs with FastAPI Zero to One: AWS Lambda with SAM and Python in One Hour AWS Storage Solutions 2022: EBS/S3/EFS/Glacier Python Bootcamp for Data Testing In Python book Minimal Python book Practical MLOps book Python for DevOps-Playlist.